TRENDS AND PATTERNS OF DRY SPELLS IN KARNATAKA - ARPITA PANDEY*; SRINIVASA SASDHAR PONNALURU (The Journal of Research ANGRAU, 2021)
Drought affects agricultural growth by its duration and frequency. Karnataka an agrarian-based economy, experienced frequent intense droughts in the last two decades. This study analyzed the intensity and duration of dry spells that occurred in Karnataka between 1990 and 2020 in the spatial context by using SPI. The Standardized Precipitation Index (SPI) helped in identifying four significant drought incidents in the last three decades. Mann-Kendall Test was used to identify the trend in the SPI values. The results showed that the droughts in last decade were more intensive compared to previous two decades. The duration of recent dry spells got overlapped between two different drought periods. The northern districts of State get more frequent dry spells compared to the southern districts.